A Triple Therapeutic Strategy with Antiexosomal Iron Efflux for Enhanced Ferroptosis Therapy and Immunotherapy. Issue 41 (7th September 2022) - Wang, Yu; Chen, Qinjun; Song, Haolin; Zhang, Yiwen; Chen, Hongyi; Liu, Peixin; Sun, Tao; Jiang, Chen
Abstract: Ferroptosis is a form of regulated cell death which can not only kill tumor cells but also enhance immunogenicity of tumor cells, and it is evidenced to be involved in a variety of tumor treatments, especially in cancer immunotherapy. Tumor cell‐derived exosomes are reported to influence the progression and metastasis process of tumors. In the process of ferroptosis, exosomes are also demonstrated as mediators to export iron under high intracellular iron concentration and resist ferroptosis. Under this regard, the combined application of ferroptosis inducer and the inhibitor of iron‐containing exosomes may enhance the ferroptosis. Herein, biocompatible hybrid nanoparticles composed of the iron oxide nanoparticles, polymers with oxaliplatin attached, and siProminin2 are constructed. The siProminin2 mediated exosomal inhibition can restore the intracellular iron concentration, which can also inhibit the secretion of tumor cell‐derived exosomes. The combination of immunotherapy with oxaliplatin, ferroptosis‐based cancer therapy and inhibition of tumor cell‐derived exosomes can enhance the immune activation effects. The nanoparticles represent an excellent triple therapeutic strategy for enhancing ferroptosis‐based cancer therapy and immunotherapy. Abstract : Biocompatible hybrid nanoparticles specifically target tumor tissues through platelet hitchhiking strategies and release drugs in response to tumor‐specific microenvironment with low systematic toxicity and good biosafety. The nanoparticles represent an excellent triple therapeutic strategy. Superior antitumor effects are achieved in triple negative breast cancer models by inhibiting exosome secretion in combination with ferroptosis‐based cancer therapy and immunotherapy.